Sistem Pengendalian Internal dan Pemanfaatan Teknologi Informasi Terhadap Nilai Informasi Pelaporan Keuangan Pemerintah Daerah - Himawan W, Sukarno; Mukoffi, Ahmad; Armita Hina Marumata, Rambu; Aprilia Dwi Suanti, Riski; Sularsih, Hermi; As’adi, As’adi (Jurnal Paradigma Ekonomika, 2023)
Abstract Study aims to examine the effect of internal control systems and the use of information technology on the value of financial reporting information. This type of research uses a quantitative approach with a total sample of 60 and uses multiple linear regression analysis techniques. The results show that the internal control system and the use of information technology have a positive effect on the value of financial reporting information partially and simultaneously Keywords: Internal Control System, Utilization of Information Technology, Value of Financial Reporting Information